The Influence of Emotional Labor on Employee Performance through Work-Life Balance as an Intervening Variable at PT Bank Mandiri, Pamekasan Regency - Putra, Arya Lucianda; Jacobis, Riedel Paulus (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the effect of emotional labor on employee performance through work-life balance as an intervening variable at PT Bank Mandiri Pamekasan Regency. This study contributes by clarifying the mediating role of work-life balance in the context of banking services. A quantitative approach was used with a saturated sampling technique involving 54 front-line employees. Data were collected through questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The results showed that emotional labor had a positive and significant effect on employee performance and work-life balance, while work-life balance also had a positive and significant effect on employee performance. In addition, work-life balance mediated the relationship between emotional labor and employee performance, which implies the importance of emotional management and work-life balance in improving sustainable employee performance.